2016
DOI: 10.3389/fonc.2016.00074
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making in the Surgical Treatment of Breast Cancer: Factors Influencing Women’s Choices for Mastectomy and Breast Conserving Surgery

Abstract: One of the most difficult decisions a woman can be faced with when choosing breast cancer treatment is whether or not to undergo breast conserving surgery or mastectomy. The factors that influence these treatment decisions are complex and involve issues regarding access to health care, concerns for cancer recurrence, and the impact of surgery on body image and sexuality. Understanding these factors will help practitioners to improve patient education and to better guide patients through this decision-making pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 71 publications
(85 reference statements)
4
55
0
Order By: Relevance
“…The role of squamous histology, if any, in selection of mastectomy in these patients needs to be evaluated in future studies. Furthermore, our study did not evaluate several factors associated with increased rates of mastectomy including the use of MRI, genetic testing results, socioeconomic factors, and several other patient characteristics [29,30].…”
Section: Discussionmentioning
confidence: 94%
“…The role of squamous histology, if any, in selection of mastectomy in these patients needs to be evaluated in future studies. Furthermore, our study did not evaluate several factors associated with increased rates of mastectomy including the use of MRI, genetic testing results, socioeconomic factors, and several other patient characteristics [29,30].…”
Section: Discussionmentioning
confidence: 94%
“…35 Comorbidities might be associated with less complete diagnostic assessment including biopsy for staging, 32,33 limited treatment options and a decreased likelihood to receive treatment with curative intent. 47 Further, SEP might influence patients treatment choice 48 and/or adherence to treatment. 49 However, studies in the canton of Geneva suggest that observed survival inequalities after BC are-at least partlycaused by differences in care management depending on SEP. 14,15 Unfortunately, information on comorbidities were not available for this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These recommendations led to a steady increase in the uptake of BCS . More recently, however, rates of mastectomy have been seen to increase in the USA, even in women with breast cancer that is suitable for BCS …”
Section: Introductionmentioning
confidence: 99%
“…A small number of women are diagnosed with cancer in both breasts and undergo bilateral surgery – usually bilateral mastectomy. In some cases, women with unilateral disease choose bilateral mastectomy to prevent cancer in the other breast, despite no clinical evidence to support any further survival benefit . In addition, an increasing option for women choosing mastectomy is to have immediate breast reconstruction, using either autologous techniques (deep inferior epigastric perforator (DIEP) artery flaps, transverse rectus abdominis myocutaneous (TRAM) flaps and latissimus dorsi (LD) flaps) or implant‐based reconstruction…”
Section: Introductionmentioning
confidence: 99%